2009
DOI: 10.1080/10589750802339687
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of natural crack initiation and its propagation in slow speed bearings

Abstract: Monitoring of bearings is an essential part of most condition monitoring programmes in rotating machinery. This paper demonstrates the use of AE measurements to detect, monitor and locate natural defect initiation and propagation in a thrust rolling element bearing. To undertake this task a special purpose test-rig was built that allowed for accelerated natural degradation of a bearing race. It is concluded that sub-surface initiation and subsequent crack propagation can be detected using a range of time and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Although conclusive, this research was not representative of broad operation condition as the test was at a slow rotational speed (72 r.p.m.). The results presented in this paper aim to compliment the work of Elforjani and Mba [7,8] by experimentally investigating the use of AE for detecting natural degradation of a bearing at a rotational speed of 1500 r.p.m. In addition, the use of the Kurtogram for improving signal-to-noise ratios on AE waveforms from a bearing is explored.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Although conclusive, this research was not representative of broad operation condition as the test was at a slow rotational speed (72 r.p.m.). The results presented in this paper aim to compliment the work of Elforjani and Mba [7,8] by experimentally investigating the use of AE for detecting natural degradation of a bearing at a rotational speed of 1500 r.p.m. In addition, the use of the Kurtogram for improving signal-to-noise ratios on AE waveforms from a bearing is explored.…”
Section: Introductionsupporting
confidence: 52%
“…Additionally, Yoshioaka terminated the test once the AE level reached a certain predefined threshold; therefore propagation of the surface defect was not monitored. Later, Elforjani and Mba [7,8] conducted an experiment that was based on Yoshioka's work. Their results showed the effectiveness of AE in detecting the onset of bearing failure, identifying the circumferential location of the defect on the race at very early stages of degradation, and the diagnostic potential of the measured AE signal by enveloping and using the KS statistic.…”
Section: Introductionmentioning
confidence: 99%
“…They also indicated that the acoustic emission method can be used to detect the subsurface crack in the bearing. Elforjani and Mba [12] used a range of time and frequency domain analysis techniques to detect a…”
Section: Zmęczeniowe Pęknięcia Podpowierzchniowe Stanowiące Jedną Z mentioning
confidence: 99%
“…Ref. [1][2][3][4][5][6][7][8][9][10]. However, all these studies are conducted based on bearing seeded defect or through modification to the bearing components.…”
Section: Research Gapmentioning
confidence: 99%
“…its fault detection capability once the bearing degrades to crack propagation [1][2][3][4][5][6][7][8][9][10]. All experimental studies conducted so far, except those by Mba and his team at Cranfield University [ [1][2][3][4][5][6]53], have focused on seeded surface spalls and scratches, and despite suggesting a higher sensitivity of AE sensors, they have not investigated the possibility of detecting subsurface cracks. In the aforementioned studies at…”
Section: Acoustic Emissionmentioning
confidence: 99%